WhatsApp, Gender, and Human Capital: Digital Communication as an Arena of Empowerment in Indonesian Families - Dwi Prasetyo; Teguh Dwi Putranto; Tia Saraswati (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This research investigates how digital communication within Indonesian families particularly through WhatsApp group chats shapes and reflects gender dynamics while contributing to the development of human capital. Using an interpretative qualitative approach, the research engaged 15 participants, including fathers, mothers, sons, and daughters aged 15 to 30, from various household structures. The findings reveal that symbolic male dominance, such as by fathers or brothers, persists in digital spaces. Meanwhile, female voices, especially those of daughters, are often muted or confined to domestic-related topics. Through the lens of Muted Group Theory and Standpoint Theory, the analysis shows that patriarchal norms are reproduced in digital interactions, yet these interactions also offer opportunities for transformation. In families practicing inclusive communication patterns, young women exhibit increased self-confidence, agency, and participation in decision-making. Family WhatsApp groups function not only as logistical tools but also as symbolic arenas where power is negotiated and emotional labor is performed. This research argues that gender-sensitive digital communication can serve as a grassroots empowerment strategy, strengthening social resilience and contributing to the development of adaptive and participatory human capital within the Indonesian cultural context.